Genotypic diversity and phenotypic spectrum of infantile liver failure syndrome type 1 due to variants in LARS1. - Lenz, Dominic; Smith, Desirée E C; Crushell, Ellen; Husain, Ralf A; Salomons, Gajja S; Alhaddad, Bader; Bernstein, Jonathan A; Bianzano, Alyssa; Biskup, Saskia; Brennenstuhl, Heiko; Caldari, Dominique; Dikow, Nicola; et al. (Genet Med, 2020)
PURPOSE: Biallelic variants in LARS1, coding for the cytosolic leucyl-tRNA synthetase, cause infantile liver failure syndrome 1 (ILFS1). Since its description in 2012, there has been no systematic analysis of the clinical spectrum and genetic findings. METHODS: Individuals with biallelic variants in LARS1 were included through an international, multicenter collaboration including novel and previously published patients. Clinical variables were analyzed and functional studies were performed in patient-derived fibroblasts. RESULTS: Twenty-five individuals from 15 families were ascertained including 12 novel patients with eight previously unreported variants. The most prominent clinical findings are recurrent elevation of liver transaminases up to liver failure and encephalopathic episodes, both triggered by febrile illness. Magnetic resonance image (MRI) changes during an encephalopathic episode can be consistent with metabolic stroke. Furthermore, growth retardation, microcytic anemia, neurodevelopmental delay, muscular hypotonia, and infection-related seizures are prevalent. Aminoacylation activity is significantly decreased in all patient cells studied upon temperature elevation in vitro. CONCLUSION: ILFS1 is characterized by recurrent elevation of liver transaminases up to liver failure in conjunction with abnormalities of growth, blood, nervous system, and musculature. Encephalopathic episodes with seizures can occur independently from liver crises and may present with metabolic stroke.
Keywords: Humans; Liver Failure; Muscle Hypotonia; Mutation; Seizures

Recurrent recessive mutation in deoxyguanosine kinase causes idiopathic noncirrhotic portal hypertension. - Vilarinho, Sílvia; Sari, Sinan; Yilmaz, Güldal; Stiegler, Amy L; Boggon, Titus J; Jain, Dhanpat; Akyol, Gülen; Dalgiç, Buket; Günel, Murat; Lifton, Richard P (Hepatology, 2016)
UNLABELLED: Despite advances in the diagnosis and management of idiopathic noncirrhotic portal hypertension, its pathogenesis remains elusive. Insight may be gained from study of early-onset familial idiopathic noncirrhotic portal hypertension, in which Mendelian mutations may account for disease. We performed exome sequencing of eight subjects from six kindreds with onset of portal hypertension of indeterminate etiology during infancy or childhood. Three subjects from two consanguineous families shared the identical rare homozygous p.N46S mutation in DGUOK, a deoxyguanosine kinase required for mitochondrial DNA replication; haplotype sharing demonstrated that the mutation in the two families was inherited from a remote common ancestor. All three affected subjects had stable portal hypertension with noncirrhotic liver disease for 6-16 years of follow-up. This mutation impairs adenosine triphosphate binding and reduces catalytic activity. Loss-of-function mutations in DGUOK have previously been implicated in cirrhosis and liver failure but not in isolated portal hypertension. Interestingly, treatment of patients with human immunodeficiency viral infection with the nucleoside analogue didanosine is known to cause portal hypertension in a subset of patients and lowers deoxyguanosine kinase levels in vitro; the current findings implicate these effects on deoxyguanosine kinase in the causal mechanism. CONCLUSION: Our findings provide new insight into the mechanisms mediating inherited and acquired noncirrhotic portal hypertension, expand the phenotypic spectrum of DGUOK deficiency, and provide a new genetic test for a specific cause of idiopathic noncirrhotic portal hypertension. (Hepatology 2016;63:1977-1986).
Keywords: Adolescent; Amino Acid Sequence; Animals; Cattle; Child; Child, Preschool; DNA Mutational Analysis; Dogs; Female; Genes, Recessive; Homozygote; Humans; Hypertension, Portal; Infant; Liver Failure; Male; Molecular Sequence Data; Pedigree; Phosphotransferases (Alcohol Group Acceptor); Principal Component Analysis; Rats; Young Adult

Individual exome analysis in diagnosis and management of paediatric liver failure of indeterminate aetiology. - Vilarinho, Sílvia; Choi, Murim; Jain, Dhanpat; Malhotra, Ajay; Kulkarni, Sanjay; Pashankar, Dinesh; Phatak, Uma; Patel, Mohini; Bale, Allen; Mane, Shrikant; Lifton, Richard P; Mistry, Pramod K (J Hepatol, 2014)
BACKGROUND & AIMS: In children with liver failure, as many as half remain of indeterminate aetiology. This hinders timely consideration of optimal treatment options. We posit that a significant subset of these children harbour known inherited metabolic liver diseases with atypical presentation or novel inborn errors of metabolism. We investigated the utility of whole-exome sequencing in three children with advanced liver disease of indeterminate aetiology. METHODS: Patient 1 was a 10 year-old female diagnosed with Wilson disease but no detectable ATP7B mutations, and decompensated liver cirrhosis who underwent liver transplant and subsequently developed onset of neurodegenerative disease. Patient 2 was a full-term 2 day-old male with fatal acute liver failure of indeterminate aetiology. Patient 3 was an 8 year-old female with progressive syndromic cholestasis of unknown aetiology since age 3 months. RESULTS: Unbiased whole-exome sequencing of germline DNA revealed homozygous mutations in MPV17 and SERAC1 as the disease causing genes in patient 1 and 2, respectively. This is the first demonstration of SERAC1 loss-of-function associated fatal acute liver failure. Patient 1 expands the phenotypic spectrum of the MPV17-related hepatocerebral mitochondrial DNA depletion syndrome. Patient 3 was found to have syndromic cholestasis due to bi-allelic NOTCH2 mutations. CONCLUSIONS: Our findings validate the application of whole-exome sequencing in the diagnosis and management of children with advanced liver disease of indeterminate aetiology, with the potential to enhance optimal selection of treatment options and adequate counselling of families. Moreover, whole-exome sequencing revealed a hitherto unrecognized phenotypic spectrum of inherited metabolic liver diseases.
Keywords: Amino Acid Sequence; Base Sequence; Carboxylic Ester Hydrolases; Child; Cholestasis; DNA Mutational Analysis; End Stage Liver Disease; Exome; Fatal Outcome; Female; Genes, Recessive; Hepatolenticular Degeneration; Heterozygote; Homozygote; Humans; Infant, Newborn; Liver Failure; Liver Failure, Acute; Male; Membrane Proteins; Mitochondrial Proteins; Molecular Sequence Data; Pedigree; Receptor, Notch2; RNA Splice Sites; Sequence Homology, Amino Acid